Analisis Sistem Antrian Dan Optimalisasi Layannan Pada Indomaret Padang Bulan Rantau Prapat - Pasaribu, Teguh Fadillah Alwi; Anistasya, Tiara; Syahfitri, Novi; Ritonga, Irmayanti (Journal of Computer Science and Information System(JCoInS), 2025)
This study aims to analyze the queuing system and optimize services at Indomaret Padang Bulan Rantauprapat. Using the Multi-Channel Single-Phase queue model, the research identifies service levels and the optimal number of cashiers needed to minimize customer waiting time, especially during peak hours. Data was collected through direct observation over three days, between 12:00 PM and 8:00 PM, with the highest arrival rate observed from 4:00 PM to 5:00 PM. Calculations were conducted using QM for Windows software. The analysis results show an average server utilization rate of 17%, with nearly zero waiting time, indicating sufficient service capacity. These findings demonstrate that with two efficiently operated cashiers, Indomaret can provide optimal services without long queues, making it one of the retail stores with the best service system.